2016
DOI: 10.12988/ams.2016.67222
|View full text |Cite
|
Sign up to set email alerts
|

Automated real-time correction of intraoperative medical tactile images: sensitivity adjustment and suppression of contact angle artifact

Abstract: Tactile perception is important for various medical applications including surgery. Currently novel devices are available that provide intraoperative mechanoreceptoric registration of tactile images. It is extremely important for endosurgery where standard palpation by surgeon's fingers is impossible. However, methods for automated analysis and even preprocessing of tactile data registered by these devices are not yet sufficiently developed. In this paper we describe two mutually reinforcing methods for prepro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Analysis of intraoperative mechanoreceptoric palpation in open surgeries confirmed that a deviation of the contact angle between the tactile mechanoreceptor and the examined tissue from 90° essentially affects tactile images registered by MTEC and complicates their interpretation. As these deviations are unavoidable in laparoscopic surgeries, specific algorithms aimed at suppression of contact angle artifacts were implemented, tested, and included in the MTEC software [ 17 ]. Currently, MTEC software also includes additional preprocessing methods that compensate for the excessive force applied to a mechanoreceptor [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of intraoperative mechanoreceptoric palpation in open surgeries confirmed that a deviation of the contact angle between the tactile mechanoreceptor and the examined tissue from 90° essentially affects tactile images registered by MTEC and complicates their interpretation. As these deviations are unavoidable in laparoscopic surgeries, specific algorithms aimed at suppression of contact angle artifacts were implemented, tested, and included in the MTEC software [ 17 ]. Currently, MTEC software also includes additional preprocessing methods that compensate for the excessive force applied to a mechanoreceptor [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…As these deviations are unavoidable in laparoscopic surgeries, specific algorithms aimed at suppression of contact angle artifacts were implemented, tested, and included in the MTEC software [ 17 ]. Currently, MTEC software also includes additional preprocessing methods that compensate for the excessive force applied to a mechanoreceptor [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were similar to the L-samples utilized in the study [17]-they were made using a soft silicone (Ecoflex 00-10, Shore hardness 00-10A) according to manufacturer's instructions and had a shape of a rectangular block with length, width, and height of 40 mm, 35 mm, and 11 mm, respectively. The difference was in sizes and shapes of hard 6 Journal of Applied Mathematics inclusions enclosed in the samples.…”
Section: Validationmentioning
confidence: 99%